2019
DOI: 10.3389/fmicb.2019.02044
|View full text |Cite
|
Sign up to set email alerts
|

Adaption of an Episomal Antisense Silencing Approach for Investigation of the Phenotype Switch of Staphylococcus aureus Small-Colony Variants

Abstract: Staphylococcus aureus small-colony variants (SCVs) are associated with chronic, persistent, and relapsing courses of infection and are characterized by slow growth combined with other phenotypic and molecular traits. Although certain mechanisms have been described, the genetic basis of clinical SCVs remains often unknown. Hence, we adapted an episomal tool for rapid identification and investigation of putative SCV phenotype-associated genes via antisense gene silencing based on previously described Tnl0-encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…aureus to the small colony variant (SCV) or persister phenotype: fabD and menD . SCVs auxotrophic for fatty acids that are more resistant to FAS-II inhibitors, such as triclosan, are associated with mutations in the fabD and fabI genes [22, 23]. SCVs auxotrophic for menadione are more resistant to aminoglycoside antibiotics, such as gentamicin, and are associated with mutations in the menD gene [15, 16].…”
Section: Resultsmentioning
confidence: 99%
“…aureus to the small colony variant (SCV) or persister phenotype: fabD and menD . SCVs auxotrophic for fatty acids that are more resistant to FAS-II inhibitors, such as triclosan, are associated with mutations in the fabD and fabI genes [22, 23]. SCVs auxotrophic for menadione are more resistant to aminoglycoside antibiotics, such as gentamicin, and are associated with mutations in the menD gene [15, 16].…”
Section: Resultsmentioning
confidence: 99%
“…The vector pRAB11(pC194 replicon) 34 was modified by PCR to restore the consensus tetO upstream of the tetR gene (IM1290/IM1291) 97 . As described previously, this reduced the impact of elevated level TetR production and allowed leaky expression of the target gene in the absence of aTc.…”
Section: Construction Of Psmbit and Plgbit Split Luciferase Vectorsmentioning
confidence: 99%
“…Schleimer et al . ( 2019 ) reported that a restoration of tetR autoregulation of pRAB11 reduced growth retardation, which was attributed to a decreased abundance of the repressor. The resulting plasmid was employed to induce AS‐RNA directed to the essential gene fabI , a gene investigated in similar studies before (Ji et al ., 2004 ; Stary et al ., 2010 ).…”
Section: Gram‐positive Solutions Of Tet Regulationmentioning
confidence: 99%
“…Six of the promoter variants were analysed and all led to lower expression levels in the induced state and tighter repression in the absence of an inducer. Schleimer et al (2019) reported that a restoration of tetR autoregulation of pRAB11 reduced growth retardation, which was attributed to a decreased abundance of the repressor. The resulting plasmid was employed to induce AS-RNA directed to the essential gene fabI, a gene investigated in similar studies before (Ji et al, 2004;Stary et al, 2010).…”
Section: Gram-positive Solutions Of Tet Regulationmentioning
confidence: 99%